Angular momentum transfer during a power tennis serve - Gordon, B. J.; Dapena, J. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
The racquet speed needed for a power tennis serve requires a large amount of angular momentum in the hand+racquet segment just before impact. This angular momentum is a function of the angular momentum acquired by the legs from the ground, and its transfer through the body to the hand+ racquet segment. The purpose of this study was to measure the transfer of angular momentum to the hand+racquet segment in a power tennis serve. Large amounts of angular momentum are first accumulated in the trunk during the backswing, and then transmitted to the racquet during the upward swing. Trunk extensor torques do not seem to play an important role in the final transmission of angular momentum to the hitting arm.